The calcineruin inhibitor cyclosporine a synergistically enhances the susceptibility of Candida albicans biofilms to fluconazole by multiple mechanisms. Issue 1 (December 2016) - Jia, Wei; Zhang, Haiyun; Li, Caiyun; Li, Gang; Liu, Xiaoming; Wei, Jun
Abstract Background Biofilms produced byCandida albicans (C. albicans ) are intrinsically resistant to fungicidal agents, which are a main cause of the pathogenesis of catheter infections. Several lines of evidence have demonstrated that calcineurin inhibitor FK506 or cyclosporine A (CsA) can remarkably enhance the antifungal activity of fluconazole (FLC) against biofilm-producingC. albicans strain infections. The aim of present study is thus to interrogate the mechanism underpinning the synergistic effect of FLC and calcineurin inhibitors. Results Twenty four clinicalC. albicans strains isolated from bloodstream showed a distinct capacity of biofilm formation. A combination of calcineurin inhibitor CsA and FLC exhibited a dose-dependent synergistic antifungal effect on the growth and biofilm formation ofC. albicans isolates as determined by a XTT assay and fluorescent microscopy assay. The synergistic effect was accompanied with a significantly down-regulated expression of adhesion-related genesALS3, hypha-related genesHWP1, ABC transporter drug-resistant genesCDR1 andMDR1, and FLC targeting gene, encoding sterol 14alpha-demethylase (ERG11 ) in clinicalC. albicans isolates. Furthermore, an addition of CsA significantly reduced the cellular surface hydrophobicity but increased intracellular calcium concentration as determined by a flow cytometry assay (p  < 0.05). Conclusion The results presented in this report demonstrated that the synergistic effect of CsA and FLC on inhibitedC. albicans biofilm formation and enhanced susceptibility to FLC was in part through a mechanism involved in suppressing the expression of biofilm related and drug-resistant genes, and reducing cellular surface hydrophobicity, as well as evoking intracellular calcium concentration.